The nuclear matrix elements of 0vββ decay and the NUMEN project at INFN-LNS. (July 2016) - Cappuzzello, F.; Agodi, C.; Aciksoz, E.; Acosta, L.; Aslanouglou, X.; Auerbach, N.; Bijker, R.; Bonanno, D.; Bongiovanni, D.; Borello, T.; Boudhaim, S.; Bouhssa, M.L.; et al.
Abstract: An innovative technique to access the nuclear matrix elements entering the expression of the life time of the double beta decay by relevant cross section measurements of double charge exchange reactions is proposed. A key aspect of the project is the use of the MAGNEX large acceptance magnetic spectrometer, for the detection of the ejectiles, and of the LNS K800 Superconducting Cyclotron (CS), for the acceleration of the required high resolution and low emittance heavy-ion beams, already in operation at INFN Laboratory Nazionali del Sud in Catania (Italy). However, a major upgrade is foreseen for the INFN-LNS research infrastructure to cope with beam currents as high as several ppA required by the project.